Tingkat Keberhasilan Perawatan Ortodonti Berdasarkan Index of Complexity Outcome and Need di Klinik Profesi Rumah Sakit Universitas Udayana - Hendrawan, Elizabeth; Anggaraeni, Putu Ika; Hutomo, Louise C.; Rahaswanti, Luh Wayan A. (e-GiGi, 2024)
Abstract: Malocclusion is a misalignment of the teeth that disrupts functional balance and causes aesthetic problems. The complexity of malocclusion, the need for treatment, and the success of treatment can be measured using the Index of Complexity, Outcome and Need (ICON). The Dental Profession Clinic at Udayana University Hospital provides health services in the field of oral health including orthodontic treatment using removable appliances. This study aimed to determine the success rate of orthodontic treatment based on ICON in patients at the Dental Profession Clinic at Universitas Udayana. This was an observational and descriptive study with a cross-sectional approach. There were 30 patients as samples selected using a purposive sampling method. The collected data were processed using descriptive statistical tests and univariate analysis, and then were presented in the form of frequencies and percentages. The results showed that 63.3% of patients were in  the substantially improved category, 16.7% in the greatly improved and moderately improved category each, and 3.3% in the minimally improved category. In conclusion, the majority of patients in this study were included in the substantially improved category. Keywords: Index of Complexity Outcome and Need (ICON); malocclusion; orthodontic appliances    Abstrak: Maloklusi merupakan penyimpangan gigi dari oklusi yang ideal, yang menganggu keseimbangan fungsional dan menyebabkan masalah estetik. Kompleksitas maloklusi, kebutuhan perawatan, dan keberhasilan perawatan dapat diukur menggunakan Index of Complexity, Outcome and Need (ICON). Klinik Profesi Rumah Sakit Universitas Udayana memberikan pelayanan kesehatan di bidang gigi dan mulut termasuk perawatan ortodonti menggunakan peranti lepasan. Penelitian ini bertujuan untuk mengetahui tingkat keberhasilan perawatan ortodonti berdasarkan ICON pada pasien Klinik Profesi Dokter Gigi Universitas Udayana. Penelitian ini menggunakan metode deskriptif observasional dengan desain potong lintang. Terdapat 30 pasien sebagai sampel penelitian yang dipilih menggunakan metode purposive sampling. Data yang terkumpul diolah menggunakan uji statistik deskriptif dan analisis univariat serta hasilnya disajikan dalam bentuk frekuensi dan presentase. Hasil penelitian menunjukkan bahwa 63,3% masuk ke dalam kategori substantially improved, 16,7% masing-masing dalam kategori greatly improved dan moderately improved, serta 3,3% dalam kategori minimally improved. Simpulan penelitian ini ialah mayoritas pasien dalam studi ini tergolong dalam kategori substantially improved. Kata kunci: Index of Complexity, Outcome and Need (ICON); maloklusi; peranti ortodonti